Explaining Peaceful Change without Democracy: The Case of the Sino-Soviet Security Community - S. Koschut (Vestnik MGIMO-Universiteta, 2019)
Some scholars have claimed that democratic regime type needs to be treated as a necessary precondition for the formation of a pluralistic security community. This essay argues that one should not overestimate the explanatory power of linking the democratic peace proposition to the study of security communities. Democratic values, norms, institutions, and practices may certainly facilitate the formation of a security community, but it is by no means the only or even most plausible path to assure dependable expectations of peaceful change. While a number of authors have of late made similar claims, what is not settled is why non-democracies can form security communities. The findings in this essay advance scholarship on this issue by showing that the same causal logics commonly attributed exclusively to democratic security community formation are also present in the formation of non-democratic security communities. The study adds empirical evidence to this argument by developing a historical case study of the Sino-Soviet relationship. In sum, the findings demonstrate that (1) democracy is not a necessary (though facilitating) precondition for the development of a pluralistic security community and (2) a pluralistic security community may form between autocratic regimes based on the causal logical nexus of non-democratic norm externalization, ideological coherence, a common Other (normative logic) and autocratic domestic institutional constraints (institutional logic).